Innovation in ant larval feeding facilitated queen–worker divergence and social complexity - Arthur Matte; Adria C. LeBoeuf (Proceedings of the National Academy of Sciences, 2025)
Building differences between genetically equivalent units is a fundamental challenge for all multicellular organisms and superorganisms. In ants, reproductive or worker fate is typically determined during the larval stage, through feeding regimes managed by adult caretakers. However, the feeding care provided to larvae varies significantly across ants, as does phenotypic divergence between queen and worker castes. Here, we employed comparative phylogenetic methods and causal inference to investigate the relationships between larval feeding care, caste size dimorphism, and social complexity across ant diversity. We digitized the life’s work of George and Jeanette Wheeler, cataloging the larval morphology of over 700 species, and we compiled data on species diets and larval feeding behaviors from the literature and our own observations. We measured queen–worker size dimorphism in 392 species and gathered data for colony size, worker polymorphism, and worker reproduction. Our analyses revealed that ancestral active-feeding larvae evolved passive morphologies when adults began feeding them individually, typically with processed material and often following a shift to nonpredatory diets. Greater queen–worker size dimorphism coevolved with larval passiveness, alongside traits indicative of increased social complexity, including larger colony sizes, worker subcastes, and a reduction in workers’ reproductive potential. Likelihood comparisons of causal phylogenetic models support that extended alloparental care facilitated stronger caste dimorphism, which, in turn and along with increased colony sizes, promoted higher social complexity. Our results suggest that enhanced adult control over larval development enabled greater phenotypic specialization within colonies, with profound implications for social evolution.